Employees/Workers Perception on Privatization - Chitrakar, Tara Devi (PYC Nepal Journal of Management, 2010)
This paper includes results of the perception survey of the major stakeholder of privatization i.e. a employees/workers on various aspects of privatization such as necessary and unnecessary means of privatization, processes and modalities followed, its impact, existing polices and role of the government, essential factor for the success of privatization etc. After preparing and administering structured questionnaire. The study had organized to survey five public enterprises from the manufacturing sector. Sample size of the employees/workers in those five enterprises was 160. Only 150 questionnaires were collected. The percentage collected being 98.8 percent. The survey was done on 2007. The studies found out that majority of employees were not in favor of privatization. They agreed in general that the majority of privatization process should go forward only after pursuing a number of essential steps including policy improvement and participation of various stakeholders.